Restorative Environment Design Drives Well-Being in Sustainable Elderly Day Care Centres - Yuting Li; Xiayan Lin; Shimin Li; Min Huang; Zhipeng Ren; Qi Song (Buildings)
At present, China is facing a serious aging problem. Although community daycare centers have been built, they generally have problems such as inadequate facilities, single-service provision, and insufficient environmental design. These problems make it impossible to meet the multifaceted needs of the elderly in their old age, enhance their sense of wellbeing, and achieve sustainable development. Therefore, relevant policies indicate that the elderly service model of community day care centers should be actively constructed and upgraded. However, most of the existing research focuses on service models or single-design practice studies, and there are relatively few studies that address the integration of restorative environmental design and sustainability. Therefore, this paper systematically explores the current research status of restorative environmental design in daycare centers for the elderly through macro quantitative bibliometric analysis and micro qualitative content analysis based on Web of Science (WOS) data, then proposes design practice strategies, implementation paths, and evaluation methods to enhance wellbeing. Through keyword network visualization analysis, this paper identifies eight main clusters: physical literacy, public preschool services, social support, elderly day care centers, hospice use, designing leisure products, risk factors, and communicative skills. The high-frequency keywords “health”, “elderly”, “cultural diversity”, “children”, and “quality of life” are further categorized into “caregiving”, “Alzheimer’s disease”, “adult day care”, and “daycare centers”, with the latter split into three further categories: design strategy, implementation approach, and evaluation. In addition, this paper combines SDG3 goals such as reducing premature mortality from non-communicable diseases, achieving universal health coverage, etc., in order to explore the potential of resilience-based environmental design to promote the sustainable development of elderly daycare centers. This study not only complements the research related to restorative environmental design in daycare centers for the elderly but also provides specific guidelines and references for future environmental design, policy planning, and elderly service practices.